Outcome comparison of African‐American and caucasian patients with severe aortic stenosis subjected to transcatheter aortic valve replacement: A single‐center experience. Issue 4 (20th May 2014) - Minha, Sa'ar; Barbash, Israel M.; Magalhaes, Marco A.; Ben‐Dor, Itsik; Okubagzi, Petros G.; Pendyala, Lakshmana K.; Satler, Lowell F.; Pichard, Augusto D.; Torguson, Rebecca; Waksman, Ron
<x xml:space="preserve">Abstract</x> Objective This study aimed to report the outcomes of African Americans (AAs) in the US undergoing transcatheter aortic valve replacement (TAVR) for severe aortic stenosis (AS). Background Compared to Caucasians, AAs are reported to have poorer outcomes from most cardiovascular diseases, including high complication rates after surgical aortic valve replacement. The outcomes of AAs undergoing TAVR are not well established. Methods Consecutive patients who underwent TAVR were included in this analysis. Patients' baseline characteristics, procedural data, in‐hospital‐ and long‐term outcomes were recorded and a comparison was performed between the AA and Caucasian cohorts. Results In a cohort of 469 consecutive patients, 51 (10.8%) were AA and 345 (74.5%) were Caucasian. The remaining patients (n = 73; 15.3%) self‐reported their race as "unknown" or were from other races. Most baseline characteristics were similar between the two groups except for less men (33.3 vs. 50.1%; P = 0.016), a lower mean left ventricular ejection fraction (48.85 ± 16.35 vs. 53.24 ± 13.41%; P = 0.04) and lower rates of atrial fibrillation in AAs (15.7 vs.45.4%; P < 0.001). TAVR procedures in AAs were less frequently performed as part of a clinical trial (60.8 vs. 76.8%; P = 0.014). Most procedural and periprocedural outcome parameters were similar save for a higher rate of hemodynamic instability and postoperative need for intubation in AAs (10.4 vs. 2.5%; P = 0.018 and 29.4 vs. 16.9%; P = 0.03, respectively). This did not translate into a difference in mortality between AAs and Caucasians (30‐day mortality 9.8 vs. 9.9%; P = 0.99; 1‐year mortality 19.6 vs. 24.3%; P = 0.458, respectively). Conclusion Unlike with other cardiovascular interventions, this study demonstrates that AA patients referred for TAVR shared similar risks and outcomes when compared to a Caucasian population. © 2014 Wiley Periodicals, Inc.